The Role of Housewives in Running a Gondo Chips Business Based on Local Wisdom - Suryawati, Dewa Ayu; Pertiwi Dewi, Si Putu Agung Ayu (Akademi Komunitas MAPINDO, 2024)
The development of tourist villages opens up opportunities for women to occupy various professions with avariety of tourism service businesses. Timpag Village is one of the villages in Tabanan Regency that empowerswomen in managing agricultural products, namely gondo vegetables into vegetable chips which are now atypical food and specialty of Timpag Village. This research aims to analyze the role of women in developingtourism icons in Timpag village and determine alternative strategies in developing gondo chips using SWOTanalysis. This research uses qualitative and quantitative descriptive data analysis techniques. Data collectiontechniques were carried out through interviews with informants, observation and documentation. Theinformants chosen for collecting data through interviews were community leaders and women's groups whomanage gondo chips. The research results show that housewives carry out three roles at once, namely domestic(household), economic role (earning a living) and social role (custom). The results of the research show thatthe strengths, weaknesses, opportunities and threats of the Gondo chips business product have been identifiedso that it can be used as a reference in formulating a strategy and model for strengthening the Gondo chipsbusiness product which requires the active role of the government and local community to participate in theeconomic development of housewives in the villages of Timpag and The role of institutions is one of the mostimportant things in developing the Gondo chips business.Keywords: Role, SWOT Analysis, Local Wisdom